Legal Framework Influence Towards E-Procurement Adoption Model in Developing Countries: Buyers’ - Suppliers’ Perception in Tanzania - Shatta, Deus N.; Layaa, John N.; Shayo, France (International Journal of Applied Research in Management and Economics, 2020)
The objective of this study was to fill the knowledge gap through analyzing the buyers’ and suppliers’ perception on legal framework influence towards e-procurement adoption model in developing countries, Tanzania in particular. This study was guided by Unified Theory of Acceptance and Use of Technology and the Technology, Organization and Environment model. The study adopted positivism philosophy and cross-sectional survey research design. The study also used non-probability (purposive) sampling and probability (stratified) sampling techniques. Sample size was 157. Questionnaires and documentary review were used for data collection. The collected data were analysed by using Partial Least Squares Structural Equation Modelling (PLS-SEM) with the help of SmartPLS 3 software. Findings reveal that in the presence of performance expectancy, relative advantage and attitude, legal framework has an indirect influence towards e-Procurement Adoption Model. The findings and recommendations of this study are anticipated to improve the adoption of e-Procurement in developing countries, Tanzania in particular.